Badania etnograficzne w regionie lubuskim = Ethnographic research in the Lubuskie Region - Pokrzyńska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the development of ethnographic research in the Lubuskie Region, highlighting key researchers, their primary areas of focus, the geographical scope of their work, and the conclusions drawn from their studies. It also examines the establishment of regional centres ? institutions pivotal to advancing ethnographic knowledge in the region - the scope of their activities, outcomes, and the influence of specific historical contexts.
Keywords: Ziemia Lubuska; kultura regionalna; badania etnograficzne; Lubuskie Region; regional culture; ethnographic research